Determinants of sustainable growth of commercial banks: Does lending growth matter? - Linggadjaya, Restiana Ie Tjoe; Atahau, Apriani Dorkas Rambu; Ugut, Gracia Shinta S; Suk, Kim Sung (International Journal of Management and Sustainability, 2025)
This study addresses a crucial aspect of the banking sector, sustainable growth, which is vital for the long-term viability of banks yet has rarely been studied. This study examines the factors affecting the sustainable growth of commercial banks and whether lending growth matters. The study uses panel data regression method with the generalized least squares and generalized method of moments with secondary data from the entire population of all listed commercial banks in Indonesia for the years 2013-2022 with a total of 399 observations. The novelty of this research is to examine the determinants of sustainable growth of commercial banks in Indonesia, including the lending growth encompassing periods of prior, during, and post-pandemic COVID-19. The results show that previous sustainable growth significantly influenced current sustainable growth, banking performance, lending growth, and capital, whereas liquidity and inefficiency had negative impacts. Contrary to previous research, loan quality had an insignificant effect, which was due to the new relaxation policy by the Indonesian Financial Services Authority to lessen the pandemic COVID-19 impact until 2024. Banks and regulators should understand the determinants of sustainable growth and be mindful of the adequacy of loan loss provision expense since it is not as ample as prior to the relaxation policy period. Future research to expand to ASEAN countries is recommended since the loans-to-GDP ratio in Indonesia is quite low and to understand the effect of different relaxation policies by different regulators.